Level up! the guide to great video game design - Rogers, Scott; Books24x7, Inc. (Chichester, West Sussex, U.K. : John Wiley & Sons Ltd, 2014)
If you want to design and build cutting-edge video games but aren't sure where to start, then the SECOND EDITION of the acclaimed Level Up! is for you! This updated edition provides clear and well-thought out examples that forgo theoretical gobbledygook with charmingly illustrated concepts and solutions based on years of professional experience. Teaches you how to develop marketable ideas, what perils and pitfalls await during a game's pre-production, production and post-production stages, and provides even more creative ideas to serve as fuel for your own projects including: Developing your game design from the spark of inspiration all the way to production; Learning how to design the most exciting levels, the most precise controls, and the fiercest foes that will keep your players challenged; Creating games for mobile and console systems - including detailed rules for touch and motion controls; Monetizing your game from the design up; Writing effective and professional design documents with the help of brand new examples. Includes all-new content, an introduction by David "God of War" Jaffe and even a brand-new chili recipe. --
Title from title screen.
Text.
Available also in a print ed.
Mode of access: Internet via World Wide Web.
Digitized and made available by: Books24x7.com.
Keywords: Computer games -- Programming; Computer games -- Design; Video games -- Design; Electronic books; Electronic books